Inequality in Teaching and Learning and the Anomaly in Educating Street Children: A Conceptual Literature Review - Julien, Gabriel (Journal of Educational Research and Practice, 2025)
Educating street children is fundamental since it provides learning opportunities and life skills. This study systematically reviews pertinent literature to explore the significance of teaching and learning and highlights the paradox in educating street children. It uses a qualitative descriptive approach and draws on various peer-reviewed sources that address inclusive pedagogical practices towards the education of street children. Mention must be made that while the literature presents worthwhile information about education and street children, it utilizes two different themes. It does not address these two headings together as one. Thus, this research fills that gap. The analysis highlights that although mainstream education does not adequately incorporate all street children, education is necessary because it frequently builds self-concept and provides children with essential strategies. The analysis notes that a healthy self-concept gives these children a sense of belonging, autonomy, and competence within their social environment. Educating street children in regular classroom settings is impossible. This paper mentions some challenges in educating street children and indicates a holistic approach to education, including curriculum design, adequate teacher training, and school inclusion policies. It also provides conceptual insights that may inform educational practitioners, policymakers, and researchers in designing meaningful educational strategies that support these children and augment their self-esteem and ability. Limitations and directions for future empirical research are also discussed.